The Fight over the Forest - Bettinger, Keith Andrew (Worldviews, 2015)
Since the fall of the authoritarian Suharto regime in Indonesia, the role of local communities in managing forest resources has been the subject of intense debate. Though the State has long asserted its authority over the country’s forest estate, local communities contend that they are the rightful owners of millions of hectares of forests, which they say has been true for centuries according to the customary rules of use, or adat. This article describes the evolution of the concept of adat beginning in the colonial era and continuing through to the present day, describing how adat has been manipulated by centralizing forces to facilitate central government control over natural resources. This discussion takes place in the context of Kerinci Seblat National Park, a large protected area on the island of Sumatra, and describes the various systems of adat found in the communities surrounding the park. The article describes how these systems have been affected by various centralizing regimes, as well as how the central government has attempted to impose resource management policies and priorities on local communities. The interaction between the central government and adat communities has in many cases led to increased environmental degradation.